Dominasi Keluarga Barmaki, Buwaihi, dan Saljuki dalam Dinamika Politik Abbasiyah - ‘Alimah, Nur; Nur Fitriani, Octaviana; Mutmainnah, Siti; Vira Nurjannah, Okta; Abbas, Ngatmin (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
The Abbasid Caliphate was one of the largest dynasties in Islamic history, experiencing various political dynamics. The power centers of the Barmaki, Buwaihi, and Saljuqi families played a crucial role in maintaining the political stability of the Abbasid Caliphate. This study aims to analyze the influence and roles of these families on the political policies and governance of the Abbasids. The method used in this research is quantitative, analyzing secondary data from historical sources and related documents. The results indicate that the Barmaki family contributed to the Abbasid golden age through efficient administration, the Buwaihi family took control through military strength and significant political influence, while the Saljuqi family played a role in political stabilization and broader territorial control. These findings reveal that the roles of these three families were significant in shaping the political landscape of the Abbasid during various periods of its rule.